The Effect of Feeding Papaya Vegetables on Breast Milk Production in Breastfeeding Mothers - Marieta K.S Bai; Hiromi Ogasawara (Universitas STRADA Indonesia, 2022)
Breast milk is a fatty emulsion in a protein, lactose and organic that is secreted by the mammary glands of mother, as the main food baby. The purpose of this study is to determine the effect of vegetables from papaya fruit to milk production in breastfeeding mothers. The research design is two group post test only control group design. The data were analyzed by univariate analysis, which treated the results of data in percentage form and bivariate analysis using Mann-Whitney test. The result obtained from univariate test analysis were most of the respondents (75.0%) with good milk production in treatment group and half of respondents (50.0%) with good milk production in the control group the Mann-Whitney test is p = 0.010 <α = 0.05. The conclusion of this research is there is influence of papaya fruits vegetation on breastfeeding production in breastfeeding mothers.